1994
DOI: 10.1088/0953-4075/27/2/008
|View full text |Cite
|
Sign up to set email alerts
|

A semiclassical model for polarization forces in collisions of electrons and positrons with helium atoms

Abstract: Abbsbact.A simple semiclassical model is proposed for the calculation of the polarization potential at short range whae the impacting electron penetrates the electron cloud of the target atom. The new method is applied to the scattering of electrons and positrons from He atoms at energies between 0.1 and 50 eV. The model is described in detail and is shown to produce a local effective potential which is computationally wry easy to devise. Calculations for electron scattering are carried out for the elastic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In our earlier calculations for helium atoms [27] we found that the present modelling of polarisation forces gave very good agreement with various existing experiments. The next step in complexity, according to the density renormalization procedure of (32), is to examine the behaviour of computed, integral and differential cross sections for neon.…”
Section: Differential and Integral Cross Sections For Neonsupporting
confidence: 87%
See 3 more Smart Citations
“…In our earlier calculations for helium atoms [27] we found that the present modelling of polarisation forces gave very good agreement with various existing experiments. The next step in complexity, according to the density renormalization procedure of (32), is to examine the behaviour of computed, integral and differential cross sections for neon.…”
Section: Differential and Integral Cross Sections For Neonsupporting
confidence: 87%
“…To correct for this, various approximate methods for damping the second-order polarisation series have been used over the years in electron-atom and electron-molecule scattering calculations [23,[29][30][31]. Recently we demonstrated that their approach could be successfully applied to the case of electron and positron scattering from the two-electron He atom [27]. In the present we show a simple, global method that provides for a smooth damping of the divergent series with terms up to fourth-order in the perturbation expansion without having to invoke any adjustable parameters for its implementation.…”
Section: Description Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parameter free damping functions 43 could also be employed but this requires the calculation of the atomic ground state electronic density and more computational effort is needed. The obtained root-mean-square deviations were 0.0042 and 0.013 meV for the H + 2 and the HeH + ions, respectively, and the largest differences between fitted and calculated energy values were 0.011 and 0.043 meV.…”
Section: A the Diatomic Curvesmentioning
confidence: 99%